Institutional Approach in Zakat Management: Perspective Bangladesh- Example from the Centre for Zakat Management (CZM) and some Suggestions - Absar, A B M Nurul (International Journal of Zakat, 2024)
This article investigates the history of the institutionalization of Zakat management in Bangladesh and presents an example from the Centre for Zakat Management (CZM). Muslims must make the obligatory charitable donation known as Zakat, one of the five fundamental tenets of Islam, to help those less fortunate in their community. Zakat is a religious tax that has been practiced in Bangladesh, a nation with a large Muslim population, for a very long time; yet, the government did not begin to formally institutionalize the practice until the late 1970s. The Islamic Foundation was given the responsibility of being the national authority in charge of Zakat collecting and distributing after the government acknowledged the significance of efficient Zakat administration in the fight against poverty and acted accordingly by establishing it as the national authority.